أثر استخدام استراتيجية التعلم المستقل في تنمية مهارة فهم المقروء لدى الطالبات من القسم الإعدادي بجامعة الراية - WIDIAS HAPSARI; ARIF TAUFIQURRAHMAN (Rayah Al-Islam, 2016)
The study aimed at uncovering the impact of the independent learning strategy in developing reading comprehension skill among the students of the second semester of the STIBA at Ar-Raayah. This study used quantitative research and experimental method. In order to achieve the objectives of the study, the researcher applies a reading comprehension test technique that examines reading skills, among others: Literal understanding skills (mahārati fahmi al-harfy), deductive understanding skills (mahārati fahmi al-istintāji), critical understanding skills (mahārati fahmi an-naqdi), language comprehension skills (mahārati fahmi tadzuki), the skill of understanding epistemology (mahārati fahmi al-ibdāi). Tests were performed in the reading comprehension technique in order to understand that the difference between the experimental group and the control group. The study was a sample of to second semester studends consisting of 30 fermale students. The sample of the study was distributed to a group 15 of students who studied the strategy on independent learning, and experimental a group consises 15 students studied according to the traditional method. The study reached the following result: The use of the independent learning strategy has an impact on the development of reading comprehension skill in STIBA Ar-Raayah. Tidentify the basic strategy that should be taken into consideration when preparing educational activities aimed at developing reading compreension skill